Diagnostic significance of bone turnover markers for predicting the risk of osteopenic syndrome in children with juvenile idiopathic arthritis - Makoviichuk, O.A.; Ilchenko , S.I.; Fialkovska, A.O. (Medicni Perspektivi, 2025)
Juvenile idiopathic arthritis (JIA) in children remains one of the world's serious medical and social problems. One of the complications of the disease is the development of osteopenic syndrome (OS) with possible formation of osteoporosis in the future. Routine methods of laboratory diagnostics of OS in children with JIA remain within normal values for a long time and therefore are unsuitable for early diagnosis of OS when there are no clinical manifestations of bone metabolism disorders. Modern instrumental methods for assessing bone mineral density (BMD) also do not characterize the speed and nature of bone metabolism. Therefore, an important addition to the methods of early diagnosis of OS in children with JIA is the assessment of biochemical markers of bone turnover (BTMs). The aim of the study was to determine the diagnostic value of bone metabolism markers for predicting the risk of osteopenic syndrome in children with JIA. 50 children with JIA aged 5 to 18 years were examined. Among the laboratory methods of investigation, in addition to general clinical ones, the determination of the content of the active metabolite of vitamin D – 25 hydroxyvitamin D (25(OH)D), osteocalcin and the marker of osteoresorption β-Cross Laps (b-ctx) in the blood serum by enzyme-linked immunosorbent assay was used. Instrumental methods of research included the assessment of BMD using an ultrasonic densitometer Sunlight Omnisense 9000. It was established that in 42% of cases, children with JIA were diagnosed with OS of varying degrees of severity. The study of serum 25(OH)D level, as an important diagnostic criterion for OS, showed that in children with OS it was significantly lower than in children without OS and amounted to 17.5 [15.7; 23.6] vs. 34.1 [22.8; 39.2] ng/ml; (p<0.05). The level of osteocalcin in children with OS was significantly lower than in children without OS (6.7 [3.9; 11.5] vs. 14.9 [9.2; 20.9] ng/mL, (p<0.05), while the level of the osteoresorption marker β-Cross Laps in children with OS was significantly higher than in children without OS (1.83 [1.48; 2.27] vs. 0.95 [0.78; 1.52] ng/mL (p<0.05). The correlation analysis revealed a positive correlation of osteocalcin level with Z-score according to densitometry (r=0.44, p<0.05) and 25(OH)D level (r=0.60, p<0.05), a negative correlation with disease activity (r= -0.88, p<0.05) and the number of active joints (r= -0.29, p<0.05). The level of the osteoresorption marker β-Cross Laps also correlated with the Z-score according to densitometry (r= -0.42, p<0.05) and 25(OH)D level (r= -0.40, p<0.05). The optimal threshold value of the levels of osteosynthesis and osteoresorption markers for the development of OS in children with JIA was determined by ROC analysis. Increased in the serum level of β-Cross Laps above 1.7 ng/ml (sensitivity – 61.9%, specificity – 89.7%, diagnostic efficiency of the test – 78.0%) and decreased in the level of osteocalcin below 8.7 ng/ml (sensitivity – 66.7%, specificity – 75.9%, diagnostic efficiency of the test – 72.0%) in the blood can be used for early diagnosis of the risk of developing OS in pediatric practice.